2016
DOI: 10.18632/oncotarget.13761
|View full text |Cite
|
Sign up to set email alerts
|

Frequent silencing of the candidate tumor suppressor TRIM58 by promoter methylation in early-stage lung adenocarcinoma

Abstract: In this study, we aimed to identify novel drivers that would be epigenetically altered through aberrant methylation in early-stage lung adenocarcinoma (LADC), regardless of the presence or absence of tobacco smoking-induced epigenetic field defects. Through genome-wide screening for aberrantly methylated CpG islands (CGIs) in 12 clinically uniform, stage-I LADC cases affecting six non-smokers and six smokers, we identified candidate tumor-suppressor genes (TSGs) inactivated by hypermethylation. Through systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…We further assessed the diagnostic effect of CDKN2A promoter methylation in HNSCC precancerous patients vs. healthy subjects. Interestingly, the AUC was 0.95 and revealed efficient diagnostic power of CDKN2A promoter methylation in diagnosis of HNSCCs from precancerous samples, which can reveal that methylation is a relatively early molecular change during carcinogenesis as previous study concluded [13,104]. Some studies have suggested that DNA methylation can be detected in body fluid samples (blood, bronchial aspirates, brushing, saliva, and urine) as a noninvasive molecular biomarker for cancer screening and diagnosis [105][106][107].…”
Section: Discussionmentioning
confidence: 72%
“…We further assessed the diagnostic effect of CDKN2A promoter methylation in HNSCC precancerous patients vs. healthy subjects. Interestingly, the AUC was 0.95 and revealed efficient diagnostic power of CDKN2A promoter methylation in diagnosis of HNSCCs from precancerous samples, which can reveal that methylation is a relatively early molecular change during carcinogenesis as previous study concluded [13,104]. Some studies have suggested that DNA methylation can be detected in body fluid samples (blood, bronchial aspirates, brushing, saliva, and urine) as a noninvasive molecular biomarker for cancer screening and diagnosis [105][106][107].…”
Section: Discussionmentioning
confidence: 72%
“…Notably, OR5T1 protein is predicted to be N-glycosylated at Asn17, suggesting the possibility that LRRC26 downregulation may be important for ORT51 glycosylation. To further identify significantly overrepresented Gene Ontology terms affected by LRRC26 expression in HCC70 cells, these upregulated or downregulated genes were analyzed using the DAVID algorithm (27,31). The most prominent cluster (annotation cluster 1; gene enrichment score, 3.12) was identified, which contained features related to 'glycoprotein', 'signal peptide', 'secreted' and 'N-linked glycoprotein (GlcNAc)' (Table VI).…”
Section: Lrrc26 Expression Negatively Regulates the Tnf-α-inducedmentioning
confidence: 99%
“…DNA methylation plays a key role in disease development. Specifically, hypermethylation can lead to stable silencing of tumor suppressor genes [21]. This process has therefore been extensively observed and studied in the context of cancer [24], [15], [41], [29].…”
Section: Introductionmentioning
confidence: 99%